The polymorphism analysis and epitope predicted of Alphapapillomavirus 9 E6 in Sichuan, China - He, Jiaoyu; Li, Qiufu; Ma, Shiyu; Li, Tianjun; Chen, Yuning; Liu, Yiran; Cui, Yanru; Peng, Jianying; Shi, Yunfan; Wei, Xia; Ding, Xianping (Virology journal, 2022)
The Alphapapillomavirus 9 (α-9 HPV) is a member of the Alphapapillomavirus genus and Papillomaviridae family. These viruses are almost all carcinogenic HPV, which is closely related to 75% of invasive cervical cancer worldwide, and has a high prevalence in Sichuan. The carcinogenic function is mainly realized by its E6 oncoprotein. Cell samples were collected by cervical scraped for HPV detecting and typing. HPV-16, HPV-31, HPV-33, HPV-52, HPV-58 5 α-9 genus HPV subtype positive samples were selected, their E6 gene was sequenced and analyzed. The positive selection sites of HPV E6 genes were estimated by PAML 4.8 server. The secondary and tertiary structure of E6 protein were predicted by PSIPred and Swiss-model. The T-cell antigen epitopes of E6 protein were predicted by IEDB. α-9 HPV has a high prevalence in Sichuan, China. From 2012 to 2017, 18,067 cell cervical samples were collected, and 3135 were detected with α-9 HPV infection. Among which, 250 cases HPV-16 E6, 96 cases HPV-31 E6, 216 cases HPV-33 E6, 288 cases HPV-52 E6 and 405 cases HPV-58 E6 were successfully amplified, 17, 6, 6, 13, and 4 non-synonymous nucleotide mutations were respectively detected in HPV-16, 31, 33, 52, and 58 E6, 7 positive selection sites of α-9 HPV E6 were selected out (D32E of HPV-16 E6, K35N, K93N and R145I of HPV-33 E6, K93R of HPV-52 E6, K93N and R145K of HPV-58 E6). The structure and antigen epitopes of E6 protein with amino acid substitution differ from those of wild-type E6 protein, especially for the mutation located in the E6 positive selection site. HPV E6 nucleotide non-synonymous mutation in the positive selection site influence the protein structure and decrease the antigen epitopes affinity of the E6 protein overall, making it more difficult for the HPV-infected cells to be detected by the immune system, and enhancing the HPV adaptability to the environment. Mutations influence the validity of HPV clinical diagnostic probes, the polymorphism analysis of α-9 HPV E6 enrich the data of HR-risk HPV in Sichuan China, and the detection probes designed with the polymorphism data in mind can improve the efficiency of clinical detection; Mutations influence epitopes affinity, the association of E6 polymorphism and epitope affinity can improve the design of therapeutic vaccine with good immunity and high generality antigen epitope; The above study all provide a good theoretical basis for the prevention and treatment of HPV-related diseases.